Researching the competence‐based curriculum: preface to a case study of four urban secondary schools. Issue 3 (1st September 2013) - Downey, Christopher; Byrne, Jenny; Souza, Ana
Abstract : This introductory article accompanies three further articles forming a case study research project undertaken to describe the experience of four urban secondary schools implementing a competence‐based curriculum for students in their first year of secondary education. The nature of such competence‐based curricula is discussed in the context of secondary schools before providing an outline of the context of each of the case study schools. A democratic and emancipatory view of education provides the rationale for the development of transferable competencies, and this is considered with respect to the challenges of engaging in a cross‐disciplinary approach to the curriculum. These challenges are viewed through the lens of Bernstein%s concepts of strong and weak framing and horizontal and vertical discourses. Each of the accompanying articles takes up a different aspect of education, focusing on curriculum planning, teaching and learning, and leadership and management respectively. Further challenges with regard to changes in the English curriculum are briefly reflected upon. Finally an outline of the case study methodology which was employed in the study is provided.